Elaboración de la curva, esfuerzo vs tiempo de un concreto de alta resistencia mediante aditamento de nanosílice, agregados mina Flores. - Berrones Galarza, Santiago Anderson (2022)
The present study is oriented towards the manufacture of a high-performance concrete with the addition of nanosilica particles. This unusual additive in construction is in the testing and study phase; being of great advantage due to the properties that it gives to all types of concrete in accordance with the research and results obtained at a national and international level, since nanosilica is a subject that has not been studied in depth when in contact with concrete. The materials to be used were obtained from the Flores mine located in the Canton Penipe in the province of Chimborazo, the cement type HE Cemento Chimborazo of high initial resistance was used, thus seeking to empower the city of Riobamba and the province of Chimborazo, promoting that the province can produce high quality and resistant aggregates. A standard sample was made without the addition of nanosilica particles and another design with these particles. In order to then be able to counteract the results of the sample with and without nanosilica, and to identify whether, thanks to this material, a better resistance is obtained together with the concrete. In the end, we obtain the stress vs. time curve and the stress vs. strain curve for high-strength concrete, as well as an ideal dosage for high-strength concrete with aggregates from the province of Chimborazo.